Avascular necrosis of the femoral head in dogs - Retrospective study - Cardoso, Catarina Borges [UNESP]; Rahal, Sheila Canevese [UNESP]; Mamprim, Maria Jaqueline [UNESP]; Oliveira, Hugo Salvador [UNESP]; Melchert, Alessandra [UNESP]; Coris, Jeniffer Gabriela Figueroa [UNESP]; Dos Reis Mesquita, Luciane [UNESP] (Universidade Federal do Rio Grande do Sul, 2018)
Background: The avascular necrosis of the femoral head is a development disease caused by ischemic necrosis, which is mainly observed in young dogs. The etiology of the disease remains controversial. The diagnosis requires imaging exams such as MRI and radiographs. Thus, the aim of the current study was to retrospectively assess a population of dogs with avascular necrosis of the femoral head in order to feature the disease, as well as to analyze the radiographic appearance of the lesion at the moment of patient consultation. Materials, Methods & Results: The signalment factors of dogs (breed, gender, age and body mass), the affected hind limb, the radiographic appearance of the lesion, the clinical signs at the moment of patient consultation, the time of occurrence and the type of treatment were evaluated. The disease was radiographically classified according to the previously described items. Forty-three cases of avascular necrosis of the femoral head were identified, 97.67% presented lameness and pain during palpation of the hip joint; and 54.34%, were 1 week to 4 months old. Females represented 58.13% of the sample, and 65.11% of them weighed from 2.6 to 4.9 kg. Based on the radiographic classification, 4.34% were Grade 1; 32.60%, Grade 2; 8.69%, Grade 3; 19.56%, Grade 4; and 34.78%, Grade 5. The femoral head and neck ostectomy was performed in 42 hind limbs (91.30%); 42.85% of the dogs reached total functional recovery and 26.19% required physiotherapy and rehabilitation. Discussion: The present sample was composed of 25 dogs, which were 6-to-11-month old at the moment of patient consultation, but 17 dogs were 12-to-36-month old at this time; only one dog was older than 36 months. It may be associated with the non-recognition of clinical signs by the owners, rather than with the late-onset form of the disease. With respect to the breed, pinscher, Yorkshire, poodle, Lhasa apso, pug were most frequently observed. However, 7 dogs were crossbreed. Such group differed from that of a review involving 188 cases encompassing West Highland white terrier, Cairn terrier and poodle as the most commonly affected breeds. No sex predilection was found in a study comprising 188 cases, but in another study comprising 14 dogs, female predilection was observed. Likewise, the females represented 58.13% of cases in the present study; and 41.86% of the participants were male. The mean body mass of the dogs in the current study was 4.33 kg, which matches the small breed dogs, which are most affected by the disease. Clinical signs of non-weightbearing lameness or an intermittent subtle lameness are common in the avascular necrosis of the femoral head. Lameness of the affected hind limb was observed in 69.76% of the cases in the present study, but 2.32% showed no lameness. Occasionally, the avascular necrosis of the femoral head is bilaterally found in 12% to 16.5% of the cases. Only 3 out of the 43 cases assessed in the present study were bilateral. Since the lesions were more frequent in Grades 2 and 5, there is less chance of success through the conservative treatment. Thus, the femoral head and neck ostectomy was the surgical procedure performed in 42 hind limbs. The procedure is used to provide pain relief and to reduce the signs of lameness. In conclusion, the population assessed in the present study was composed of small size dogs, mean body mass 4.33 kg, no sex predilection, mostly presenting unilateral lesions and higher Grade 2 and Grade 5 radiographic lesion frequency.
Keywords: Canine; Hip; Joint; Radiographic